2020
DOI: 10.3390/nano10061146
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Plant and Microbe-Based Synthesis of Metallic Nanoparticles and Their Antimicrobial Activity against Plant Pathogens

Abstract: A large number of metallic nanoparticles have been successfully synthesized by using different plant extracts and microbes including bacteria, fungi viruses and microalgae. Some of these metallic nanoparticles showed strong antimicrobial activities against phytopathogens. Here, we summarized these green-synthesized nanoparticles from plants and microbes and their applications in the control of plant pathogens. We also discussed the potential deleterious effects of the metallic nanoparticles on plants and benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(75 citation statements)
references
References 188 publications
1
73
0
1
Order By: Relevance
“…The FTIR analysis was used to reveal the occurrence of different functional groups that are accountable for the long-term stabilization of ZnONPs [ 46 ]. In addition, these functional groups also demonstrated the presence of macromolecules including proteins, sugars, lipids, nucleic acids, and carbohydrates that ensure the stability of biogenic ZnONPs [ 47 ]. In this study, the FTIR spectra of biogenic ZnONPs presented different absorption peaks at 3374, 2968, 1644, 1407, and 1058 cm −1 including a weak peak at 621 cm −1 ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR analysis was used to reveal the occurrence of different functional groups that are accountable for the long-term stabilization of ZnONPs [ 46 ]. In addition, these functional groups also demonstrated the presence of macromolecules including proteins, sugars, lipids, nucleic acids, and carbohydrates that ensure the stability of biogenic ZnONPs [ 47 ]. In this study, the FTIR spectra of biogenic ZnONPs presented different absorption peaks at 3374, 2968, 1644, 1407, and 1058 cm −1 including a weak peak at 621 cm −1 ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies has appeared on the green synthesis of Ag and Au NPs using plant extracts as reducing agents [ 18 , 19 ]. Ganesan et al reported the preparation of spherical shaped, ~10 nm sized Au NPs using an aqueous extract of Acorus calamus rhizome as the reducing agent [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetal extracts are a good choice for "green" synthesis of metallic nanoparticles, since plant extracts contain many bioactive compounds (aminoacids, proteins, enzymes, polysaccharides, organic acids, polyphenols, flavonoids, terpenoids, tannins, etc.) that can bioreduce and stabilize the nanoparticles [270]. We could choose a plant or a plant mixture, taking into account their health benefits.…”
Section: Nanotechnology In Starch Food Packagingmentioning
confidence: 99%